‘The House of Archelaos’: Archaeological Investigations of the State Hermitage Expedition in Quarter XX of the Tauric Chersonesos in 2014–2018 - Novoselova, Nadezda (Hyperboreus, 2019)
A survey of the excavations of the State Hermitage Expedition in Quarter XX of the Tauric Chersonesos in 2014–2018.